The Body, Illness and Partial Disability - Skrzypek, Michał; Kowal, Katarzyna (The Body and Sociology – empirical research and theoretical concepts, 2026)
The chapter offers the sociological perspective on chronic diseases and disability, and focuses attention on the effort related to identity forming. M. Merleau-Ponty initiates the reflection on this issue by describing the perceived possession of a non-existent limb (phantom limb syndrome). D. Leder notes that a dysfunction of the body causes the body to enter the stream of consciousness; it becomes an experienced phenomenon and leaves the “„corporal” background. Including the biological dimension of the body in socio-medical research is postulated by S. Timmermans and S. Haas, who propose the sociology of particular chronic diseases defined on the basis of their clinical criteria. A complete picture of the identity-related consequences of chronic diseases and disability is offered in the works of K. Charmaz. Furthermore, the reflection presented by Anselm Strauss et al. emphasises the value of the interactive dimension of the body; the body is a non-negotiable condition for taking actions and engaging in interactions. The discussed theories emerge from qualitative studies conducted in groups of chronically ill persons. K. Charmaz argues that these persons report on their suffering using “„the language of loss”, which refers to the aspects of the <self> that were modified due to bodily changes. K. Yoshida describes the effort related to one’s personal identity that is made by persons with spinal cord injury. In his research involving people after proctocolectomy, M. Kelly documented the bodily roots of social interactions. The sociological analyses of the identity-related issues initiated by bodily changes supplement the biomedical perspective on disease and incomplete agency, providing knowledge regarding the processes occurring in one’s psycho-social sphere.